Inisiasi Pendampingan Pengelolaan Limbah B3 Domestik di Era Pandemi Covid-19 - Prasasti, Corie Indria; Yudhastuti, Ririh; Sulistyorini, Lilis; Adriyani, Retno; Sudarmaji, Sudarmaji; Zahro, Alif Fatimatuz; Kurnia, Galuh Mega (Universitas Pahlawan Tuanku Tambusai, 2025)
Increased volumes of domestic hazardous waste, especially during the pandemic, pose a serious challenge to health and the environment. In Medokan Ayu Village, Surabaya City, ineffective waste management has the potential to harm the community and the environment. Therefore, this community service activity aims to train housewives in identifying and managing domestic B3 waste in a safe and integrated manner. The method applied includes three stages: preparation, implementation, and evaluation. In the implementation stage, socialization, training on waste sorting and labeling, and assistance in establishing waste banks were conducted through lectures, discussions, demonstrations, and hands-on practice. The evaluation results showed that 90% of the participants could practice B3 waste management correctly. In addition, 7 waste banks were formed in each RT that support waste management and provide economic benefits, with an income of up to Rp300,000 per RT. In conclusion, this activity succeeded in increasing community awareness and skills in effectively managing hazardous waste. This model can be replicated to support sustainable waste management in other areas.